(untitled) (Semiárida, 2020)
Agrotis robusta is a species of moth belonging to the complex of cutworms that cause damage in summer crops in the Región Semiárida Pampeana. A tool used to control Lepidoptera are the "Bt corn", transgenic crops that incorporate insecticidal proteins from the bacterium Bacillus thuringiensis. The objective of this work was to determine the effect produced by different biotechnological events of corn on the consumption of leaf area, weight and mortality of Agrotis robusta larvae. For this, larvae were fed for 10 days with foliar tissue from five hybrids of "Bt corn": Herculex(HX), Maizgard(MG), Powercore(PW), Agrisure Viptera3(VIP3), VT Triple Pro(VT3P), corn without transgenic events for insect resistance (NBT) and a blank treatment with wild quinoa (Q). An experimental design in random blocks with three repetitions was arranged. The weight of the larvae, consumption and mortality was evaluated. The PW, VT3P and VIP3 corn hybrids, which incorporate more than one Bt toxin, produce a decrease in leaf area consumption and weight loss in A. robusta larvae. The highest mortality is observed in the PW treatment, followed by VT3P and VIP3. The hybrids MG and HX record a consumption of leaf area, weight and mortality of larvae similar to the NBT treatment